PENGARUH KOMITMEN ORGANISASI, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) SUMEKAR SUMENEP - jurnalmap map; Muhammad Hasyim Asyari; Chamariyah ÔÇì; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Sumekar Sumenep Islamic People Financing Bank (BPRS). The purposes of this study are 1). To describe the organizational commitment, compensation motivation and performance. 2). To find out whether organizational commitment, motivation and compensation have a simultaneous influence on the performance. 3). To find out whether organizational commitment, motivation and compensation have a partial effect on the performance. 4). To find out which variables among organizational commitment, motivation and compensation have a dominant influence on the performance. The results of the study show that: 1). Simultaneously, organizational commitment, motivation and compensation have a significant effect on the performance of Sumekar Sumenep Bank Islamic finance (BPRS) employees, 2). Partially organizational commitment, motivation, compensation partially have a significant influence on the performance of employees of the Bank of Islamic finance (BPRS) Sumekar Sumenep. Keywords: Organizational Commitment, Motivation, Compensation And Performance Of Employees.